A Theoretical Study on Terpene‐Based Natural Deep Eutectic Solvent: Relationship between Viscosity and Hydrogen‐Bonding Interactions. Issue 3 (12th January 2021) - Fan, Chen; Liu, Yang; Sebbah, Tarik; Cao, Xueli
Abstract: The aim of this work is to shed light on the origins of unique properties by studying the relationship between viscosity and hydrogen‐bonding interactions of terpene‐based natural deep eutectic solvents (NADES). Five systems including camphor/formic acid, menthol/acetic acid, menthol/β‐citronellol, menthol/lactic acid, and thymol/β‐citronellol are prepared (molar ratio 1:1). Their structures and nature of the associated hydrogen bonds are investigated through multiple methods and theories. The viscosity of NADES is consistent with the product of hydrogen‐bond number and lifetime. Through visualization of non‐covalent interactions, terpene‐acid‐based NADES with single sites show the lowest viscosity among the studied systems because of weak and unstable hydrogen bonding. Inversely, multi‐site terpene‐acid‐based NADES possess relatively high viscosity. Owing to the stability of hydrogen bonds in the network, the terpene‐terpene‐based system is in the middle level of viscosity. In‐depth analysis of these hydrogen bonds shows that they can be classified as "weak to medium" and are mainly derived from electrostatic interactions. Moreover, there is an obvious connection between viscosity and hydrogen‐bonding strength (integrated core‐valence bifurcation index) in the networks. The discovery of intrinsic rules between viscosity and hydrogen‐bonding interactions is beneficial for the design of novel low‐viscosity NADES in the future. Abstract : The structures and inner nature of the hydrogen‐bond network of different systems are studied by multiple methods. The discovery of intrinsic rules between viscosity and hydrogen‐bonding interactions is beneficial for the rational and effective design of novel low‐viscosity natural deep eutectic solvents.